Environmental health and human health-unifying strategies, conceptual framework and green prescriptions: a review - Chandar, Deepika; Ravipragasam, Surendar (International Journal Of Community Medicine And Public Health, 2024)
The intricate relationship between environmental conditions and human health is increasingly acknowledged as a critical area of public health research. As global challenges such as climate change, urbanization, and biodiversity loss become more pronounced, understanding the connections between these environmental factors and health outcomes is essential for developing effective public health strategies. This analysis delves into the complex interactions that exist between environmental influences and health, emphasizing the urgent need for integrated approaches that simultaneously promote ecological sustainability and enhance community well-being. Environmental degradation has significant implications for human health, with many deaths linked to preventable environmental health risks. These risks encompass a wide range of issues, including air and water pollution, exposure to hazardous substances, and the impacts of climate change, all of which disproportionately affect vulnerable populations. A conceptual framework is proposed to elucidate the multifaceted connections between environmental exposures, health determinants, and health outcomes, enabling a clearer understanding of how these elements interrelate. Cohesive strategies, such as the one health approach, advocate for collaboration across various sectors, including public health, veterinary health, and environmental management, to address the shared challenges of health and environmental degradation. Additionally, the principles of planetary health highlight the interdependence of ecosystems and human well-being, underscoring the need for sustainable management of natural resources to safeguard health outcomes. This article also explores the concept of "green prescriptions," which involve recommending nature-based interventions to enhance physical, mental, and social well-being. These prescriptions have demonstrated effectiveness in promoting health while fostering a sense of environmental stewardship. By synthesizing current evidence and successful case studies, this review emphasizes the significance of adopting a holistic perspective that integrates environmental considerations into healthcare practices. Ultimately, fostering collaboration among various stakeholders will contribute to the development of resilient communities that are better equipped to navigate the intertwined challenges of health and environmental sustainability.